2015
DOI: 10.1021/acsami.5b06876
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Graphene Oxide: How Sharp Edged Structure and Charge Matter

Abstract: Graphene oxide and its derivatives have been widely explored for their antimicrobial properties due to their high surface-to-volume ratios and unique chemical and physical properties. However, little information is available on their effects on viruses. In this study, we report the broad-spectrum antiviral activity of GO against pseudorabies virus (PRV, a DNA virus) and porcine epidemic diarrhea virus (PEDV, an RNA virus). Our results showed that GO significantly suppressed the infection of PRV and PEDV for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
333
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(337 citation statements)
references
References 60 publications
3
333
1
Order By: Relevance
“…In spite of the graphene oxide, microscopy studies show that morphology of virions does not change upon interactions with the functionalized graphene sheets. To obtain further evidence for the potential of suitably functionalized graphene sheets to bind viruses, in vitro assays were carried out.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of the graphene oxide, microscopy studies show that morphology of virions does not change upon interactions with the functionalized graphene sheets. To obtain further evidence for the potential of suitably functionalized graphene sheets to bind viruses, in vitro assays were carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene is a single‐atom thick 2D carbon allotrope with both, high structural stability and flexibility at the same time. Its large surface area and unique physicochemical properties make it very interesting for biomedical applications, such as detection and incapacitation of different types of pathogens . Inspired by multivalent heparan sulfate mimetic nanomaterials, such as sulfated gold nanoparticles or graphene oxide, polysulfated graphene could be considered as a bioactive surface for multivalent interactions with biological structures, such as viruses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have shown that the interaction between graphene-family 2D materials and bacteria, viruses as well as fungi could lead to strong antibacterial, 267270, 276 antiviral 272, 273 and antifungal 268, 274, 275 activities. For example, the antibacterial activity of graphene and GO sheets might be attributed to damage on bacterial membranes induced by the atomically sharp edges of the 2D sheets as demonstrated in Fig.…”
Section: Fundamental Modes Of Biological Interactionmentioning
confidence: 99%
“…In some other studies, it was reported that the negative charges on GO and rGO along with their unique single‐layer structure were enough to bind and thus suppress the infection of the pseudorabies virus (PRV, a DNA virus) and porcine epidemic diarrhea virus (PEDV, an RNA virus) . Comparison experiments confirmed that both the negative charges and nanosheet structure contributed to their antiviral ability . It was further shown that heat treatment could enhance virus capture and even denaturation due to the excellent heat and electron transfer properties of GO or rGO …”
Section: Interactions Between Graphene Derivatives and Pathogensmentioning
confidence: 89%